Risk stratification in middle-aged patients with congestive heart failure: prospective comparison of the Heart Failure Survival Score (HFSS) and a simplified two-variable model - Zugck, Christian; Krüger, Carsten; Kell, Robert; Körber, Sven Christopher; Schellberg, Dieter; Kübler, Wolfgang; Haass, Markus (European journal of heart failure, 2001)
The performance of a US-American scoring system (Heart Failure Survival Score, HFSS) was prospectively evaluated in a sample of ambulatory patients with congestive heart failure (CHF). Additionally, it was investigated whether the HFSS might be simplified by assessment of the distance ambulated during a 6-min walk test (6′WT) instead of determination of peak oxygen uptake (peak VO2).
Gesehen am 04.06.2021